DEVELOPING READING COMPREHENSION QUESTIONS OF PROCEDURE TEXT USING HIGHER ORDER THINKING SKILL IN ENGLISH TEXTBOOK OF GRADE ELEVEN AT SMA YAYASAN NURUL ISLAM INDONESIA BARU MEDAN - Afanin Nabila; Rahmad Husein (Universitas Negeri Medan, 2020)
The development of HOTS-based text questions is considered very important to be developed for high school students. based on the objectives of the 2013 Curriculum education unit which states that